Proceedings of the 2nd ACM MobiCom Workshop on Drone Assisted Wireless Communications for 5G and Beyond 2020
DOI: 10.1145/3414045.3415941
|View full text |Cite
|
Sign up to set email alerts
|

Private blockchain-envisioned security framework for AI-enabled IoT-based drone-aided healthcare services

Abstract: Internet of Drones (IoD) architecture is designed to support a coordinated access for the airspace using the unmanned aerial vehicles (UAVs) known as drones. Recently, IoD communication environment is extremely useful for various applications in our daily activities. Artificial intelligence (AI)-enabled Internet of Things (IoT)-based drone-aided healthcare service is a specialized environment which can be used for different types of tasks, for instance, blood and urine samples collections, medicine delivery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…These encryption techniques provide the secrecy to the stored data as well the data, which is in transit. 12,16 • Integrity of health records: BIPHRS's should be protected against any kind of unauthorized updating. To maintain the integrity, the PHR, we should utilize the hash algorithms, that is, SHA256.…”
Section: Security Requirements In Biphrsmentioning
confidence: 99%
“…These encryption techniques provide the secrecy to the stored data as well the data, which is in transit. 12,16 • Integrity of health records: BIPHRS's should be protected against any kind of unauthorized updating. To maintain the integrity, the PHR, we should utilize the hash algorithms, that is, SHA256.…”
Section: Security Requirements In Biphrsmentioning
confidence: 99%
“…It is then extremely helpful for the people who are with the compromised immunity and do not want to visit the hospitals physically. On the basis of reports generated through the collected samples, the doctors of a relevant hospital can prescribe the required medicines to the patients [5]. • Smart farming: IoD is also very useful for the smart farming/agriculture as the farmers always look for cheap and effective techniques for the regularly monitor of their crops (farms).…”
Section: A Iod Applicationsmentioning
confidence: 99%
“…Access control and authentication are two important security services to secure different networking environments, like IoT, IoD, Internet of Vehicles (IoV), Wireless Sensor Networks (WSNs), cyber-physical systems, smart grids, healthcare services, etc. [3]- [5], [16]- [31]. Tian et al [32] suggested a "certificate-based privacypreserving authentication scheme for an IoD environment".…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In health care, UAVs have been used for preventing cyber-attacks [28], information distribution [29], medical supplies dispatch, and others [30]. In healthcare, these AI-powered UAVs have been used for surveillance to combat pandemics [31], blockchain-envisioned security framework for AI-enabled IoT-based drone-aided healthcare services [32], and smart communication systems [33]. Other studies have proposed using mixed 5G and AI-powered UAVs for various applications in healthcare as means for transformation into a smart healthcare sector [34].…”
Section: Introductionmentioning
confidence: 99%